Menyusun Program Humas - Fathoni, Wiildan; Ritonga, Nurhayani; Mahdayeni, Mahdayeni (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Public relations (PR) is a strategic managerial function that plays an important role in building communication, image, and public trust in educational institutions. In the context of modern societal development and advances in information technology, educational institutions are required to manage public relations in a professional, well-planned, and sustainable manner. This study aims to comprehensively examine the concepts, stages, implementation, and evaluation of public relations program planning in educational institutions, particularly from the perspective of public relations management and Islamic educational values. This research employs a qualitative approach using a library research method. Data were obtained from various secondary sources, including academic books, journal articles, educational regulations, and official documents relevant to public relations management. Data analysis was conducted through content analysis by synthesizing experts’ perspectives in a descriptive-analytical manner. The findings indicate that effective public relations program planning must follow systematic stages, including situation analysis, goal setting, target identification, formulation of strategies and messages, planning of activities and media, budgeting, and the determination of performance indicators. The implementation of public relations programs requires internal coordination, two-way communication with the public, appropriate media management, and the application of ethics and professionalism. Evaluation of public relations programs serves as a basis for improvement and managerial decision-making. This study confirms that well-planned and ethical public relations programs are capable of strengthening institutional image, increasing public trust, and supporting the overall success of educational management, particularly in Islamic educational institutions.